Oral Squamous Cell Carcinoma Arising from Oral Submucous Fibrosis – A Comparative Retrospective Study with an Insight into the Pathogenesis - Suvarna Kizhakkoottu; Abilasha Ramasubramanian; Pratibha Ramani (Journal of Head & Neck Physicians and Surgeons)
Background: Oral squamous cell carcinoma (OSCC) with oral submucous fibrosis (OSMF) is one of the most prevalent clinical presentations in Southeast Asian nations and its pathological features have been a topic of interest. The aim of the present study is to analyze and compare the clinicopathological parameters of OSCC with OSMF with conventional OSCC and to suggest a possible pathogenic mechanism of OSCC with OSMF. Materials and Methods: The present retrospective study included a total sample size of n = 90 (OSCC with OSMF = 45, OSCC = 45). A random sampling method based on clinical and pathological reports was used for selecting the OSCC and OSCC with OSMF cases of buccal mucosa origin. Clinicopathological features were evaluated by two independent pathologists, and IBM SPSS 26 was used for statistical evaluation. Pearson Chi-square test and binary logistic regression were carried out for evaluating the association of pathological parameters between cases and controls. Cramer’s V-test was used for assessing the strength of association. Results: When compared to conventional OSCC, OSCC with OSMF patients showed a positive habit history (P = 0.00), less poorly differentiated cases (P = 0.01), minimal number of cases with advanced tumor staging (P = 0.001), decreased nodal metastasis rate (P = 0.005) and reduced depth of invasion (P = 0.001). Conclusion: OSCC arising from OSMF behaves clinicopathologically differently when compared to conventional OSCC in terms of habit history association, tumour differentiation, cervical metastasis, depth of invasion and pathological staging. However, to consider OSCC with OSMF as a separate clinicopathological entity requires multiple multicenter studies from variable geographical area with larger sample sizes and precise sampling criteria.